Efektivitas Program Penjenjangan Kinerja Organisasi Perangkat Daerah pada Badan Perencanaan Pembangunan Daerah di Kota Pariaman - Indah Safira, Putri; Malau, Hasbullah (PUBLICNESS: Journal of Public Administration Studies, 2023)
This study aims to find out how the effectiveness of the Regional Apparatus Organizational Performance Program (OPD) at the Regional Development Planning Agency (BAPPEDA) in Kota Pariaman, and the factors that influence the effectiveness of the Regional Apparatus Organizational Performance Program (OPD) at the Regional Development Planning Agency (BAPPEDA) in Pariaman City. This research was conducted in Kota Pariaman using qualitative analysis techniques with descriptive methods, namely the results of interviews, observations, and documentation studies. The results of the study found that the Effectiveness of Regional Apparatus Organizational Performance (OPD) Regional Development Planning Agency (BAPPEDA) in Pariaman City according to the indicators it can be said that four indicators are generally effective including target success, program success, program satisfaction, goal attainment, while output level and input in general its application has not been effective. Factors influencing the Effectiveness of the Regional Apparatus Organizational Performance Program (OPD) at the Regional Development Planning Agency (BAPPEDA) in Kota Pariaman consist of two, namely Human Resources and Budget Limitations.